2012
DOI: 10.1002/chem.201102809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alcohol Structures on the Interaction Mode with the Hexameric Capsule of Resorcin[4]arene

Abstract: After more than a century of research on resorcin[4]arenes (1) it is clear that such systems form spontaneously [1(6)(H(2)O)(8)]-type hexameric capsules in wet, non-polar, organic solvents. However, the interactions of these hexameric capsules with alcohols are far from being solved. Here we provide the results of an extensive study on the interaction of different alcohols with the hexameric capsules of resorcin[4]arene 1a by focusing on the exchange of magnetization manifested in diffusion NMR measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Of particular interest were alcohol additives, as their interactions with the resorcinarene capsule are well documented. 15,[35][36][37] The Cohen group investigated the incorporation of different alcohols into the resorcinarene capsule in solution and demonstrated that they can replace water molecules of the hydrogen bond network. 15,36 Additionally, in the solid state it was reported that the incorporation of nPrOH into the hydrogen network of the resorcinarene hexamer results in 25% larger assemblies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest were alcohol additives, as their interactions with the resorcinarene capsule are well documented. 15,[35][36][37] The Cohen group investigated the incorporation of different alcohols into the resorcinarene capsule in solution and demonstrated that they can replace water molecules of the hydrogen bond network. 15,36 Additionally, in the solid state it was reported that the incorporation of nPrOH into the hydrogen network of the resorcinarene hexamer results in 25% larger assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…15,[35][36][37] The Cohen group investigated the incorporation of different alcohols into the resorcinarene capsule in solution and demonstrated that they can replace water molecules of the hydrogen bond network. 15,36 Additionally, in the solid state it was reported that the incorporation of nPrOH into the hydrogen network of the resorcinarene hexamer results in 25% larger assemblies. 38 These reports prompted us to investigate the inuence of different alcohol additives on the iminium catalysis inside I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c,15c,18 Furthermore, it was shown that suitable alcohol molecules can be integrated into the hexameric structure by replacing some of the water molecules. 19 The guest exchange is overall facile and is believed to occur through a pentameric intermediate via dissociation of one resorcin [4]arene subunit. 20 Like in similar systems, the guest encapsulation can be analyzed via 1 H NMR spectroscopy, taking advantage of the aromatic anisotropy of the cavity walls, and via NOESY and DOSY ex- Intrigued by the good encapsulation of tertiary amines, the Tiefenbacher group recently discovered the Brønsted acidic character of the resorcin [4]arene hexamer.…”
Section: Molecular Capsules: Structures and Backgroundmentioning
confidence: 99%
“…Encapsulation was evidenced by 1 H, DOSY and NOESY NMR. 19 F NMR indicated that the triflate anion was not encapsulated. The cationic catalyst is likely coordinated by water.…”
Section: Syn Thesismentioning
confidence: 99%